Contribuição do assistente social para a justiça na área da infância e da juventude: o laudo social e a aplicação da lei - encontros e desencontros - Fuziwara, Aurea Satomi (2006)
From the gathered information concerning the social worker performance related to the Judicial Power, the goal of this research is to bring up the joint action of this professional in cases related to child and adolescent rights. Viewing the expressions of contemporary social issues, there is also a reflection on the science role now, approaching ideological expressions and its implications in the adopted methodologies. The reflections on instrumentality, teleology and professional ethics were inherent to the research sequence. In addition, this research is guided by an ideopolitical horizon. This set of elements appears in the lines, which support this analysis. In relation to the field research, jurisprudential cases were elected, in which conformed conflicts are expressed in a civil action. Among the cases judged in ten years (1991 to 2001), an intentional sample with significant cases was extracted. Eight cases were wholly studied and three cases presented in detail due to their complexity and for the study relevance. It is affirmed that law professionals acknowledge the importance of the social worker performance because it supplies them with data to support their performance, so the research brought up the elements used in this way. Also, oriented through a criticalpropositive prospective, it identified some fragilities. Therefore, the study makes evident some clues for a professional exercise that contributes for not only law enforcement, but also mainly for decisions which are the most beneficial in order to bring into effect social justice and rights